Ischemic stroke in anti-β2-glycoprotein I IgA-associated non-criteria antiphospholipid syndrome: a case report of arterial recanalization via antiplatelet therapy - Liu, Jihong; Chen, Yanru (Frontiers in Immunology, 2025)
BackgroundThe pathogenic potential of non-criteria antiphospholipid antibodies (aPLs), such as anti-β2-glycoprotein I (aβ2GPI) IgA, remains undefined. Additionally, the role of antiplatelet therapy in thrombotic antiphospholipid syndrome (APS) is controversial. Diagnosing APS is challenging when consensus aPLs are negative. Arterial recanalization via antiplatelet therapy in thrombotic APS has not been reported so far.Case presentationA 65-year-old woman presented with acute basilar artery occlusion. Dual antiplatelet therapy (aspirin + clopidogrel) achieved complete arterial recanalization within 11 days. High-Resolution Magnetic Resonance Imaging excluded atherosclerosis, dissection, or arteritis. Cardiac evaluations ruled out cardioembolism. Laboratory tests revealed persistent isolated high-titer aβ2GPI IgA (>150 U/mL) with negative consensus aPLs. Thrombotic workup excluded hereditary or other secondary thrombophilia, supporting a diagnosis of non-criteria APS. Long-term aspirin monotherapy maintained vascular patency and prevented stroke recurrence over 5 years.ConclusionThis case highlights the thrombogenic role of aβ2GPI IgA in seronegative APS and demonstrates the potential efficacy of antiplatelet therapy, a strategy not prioritized in current APS guidelines favoring anticoagulation therapy, in reversing arterial occlusion and preventing recurrence in non-criteria APS. It underscores the need to re-evaluate diagnostic criteria and therapeutic strategy for seronegative APS with non-criteria aPLs.